2017
DOI: 10.5811/westjem.2017.6.33414
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of A “No Superuser Opioid Prescription” Policy On ED Visits And Statewide Opioid Prescription

Abstract: IntroductionThe U.S. opioid epidemic has highlighted the need to identify patients at risk of opioid abuse and overdose. We initiated a novel emergency department- (ED) based interventional protocol to transition our superuser patients from the ED to an outpatient chronic pain program. The objective was to evaluate the protocol’s effect on superusers’ annual ED visits. Secondary outcomes included a quantitative evaluation of statewide opioid prescriptions for these patients, unique prescribers of controlled su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Each of the studies that measured the frequency of ED visits (n = 12) reported a decrease in the number of visits following the implementation of an intervention. [19][20][21][22][23][24][25][26][28][29][30][31] Nine of the studies reported statistically significant reductions in the frequency of ED visits (from p < 0.0001 to p < 0.05), 19,22,23,[26][27][28][29][30][31] one reported a nonsignificant reduction (p = 0.68), 21 and two studies did not report a p value. 19,24 • Patients referred to taper-to-abstinence pain management clinic run by a pain management and addiction specialist;…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Each of the studies that measured the frequency of ED visits (n = 12) reported a decrease in the number of visits following the implementation of an intervention. [19][20][21][22][23][24][25][26][28][29][30][31] Nine of the studies reported statistically significant reductions in the frequency of ED visits (from p < 0.0001 to p < 0.05), 19,22,23,[26][27][28][29][30][31] one reported a nonsignificant reduction (p = 0.68), 21 and two studies did not report a p value. 19,24 • Patients referred to taper-to-abstinence pain management clinic run by a pain management and addiction specialist;…”
Section: Discussionmentioning
confidence: 94%
“…The types of opioid medications considered in the analyses of the studies that measured this outcome (n = 5) were hydromorphone, oxycodone, hydrocodone, tramadol, and codeine. 20,22,24,26,27 The method of measurement varied widely across studies with some reporting pill count, total number of prescriptions, or proportion of patients who received an opioid prescription. Regardless of the unit of measurement, all studies reported a statistically significant reduction in the number of opioid prescriptions following the implementation of their respective intervention (p < 0.05 to p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations